Impact of ESG Disclosure, Investment Decisions, and Leverage on Firm Value in Indonesian Banking 2019-2023 - Ningtyas, Firda Alfi; Sartika, Sartika; Ekawati, Sarumaha Siska; Indri, Dea; Kustina, Lisa (Lentera Ilmu Nusantara, 2025)
This study aims to determine whether environmental, social, and governance (ESG) disclosures, investment decisions, and leverage have an effect on company value. This research method uses quantitative research. The sample in this study was 10 banking companies listed on the Indonesia Stock Exchange (IDX) obtained using the purpose sampling method and observation years during 2019 - 2023. The type of data used is secondary data. Data collection was carried out using financial reports (Annual reports) and sustainability reports. These results indicate that environmental and social disclosures do not affect company value, while governance disclosures affect company value. Investment decisions have a significant effect on the company and leverage does not have a significant effect on company value. These findings provide useful insights for banking institutions to prioritize strong governance mechanisms in ESG reporting and optimize investment decision-making, thereby enhancing their overall firm value and stakeholder trust.